A Study to Assess the Neurocognitive Pro?le of Patients with OCD and Depression - Reddy, Musuku Srikanth (Asian Journal of Medical Research, 2020)
Background: The present study was conducted to assess the neurocognitive profile of patients with OCD and depression. Subjects & Methods: It comprised of patients of OCD (42) and depression (42) of both genders. An equal number of healthy control was also recruited. VAIS and performance tests of intelligence (BSS) were recorded. Results: Group I had 22 males and 20 females, group II had 18 males and 24 females and group III had 21 males and 21 females. The value for VAIS and performance tests of intelligence (BSS) parameters such as information were 94.2, 96.4 and 98.3 in all groups respectively, digit span was 103.4, 102.5 and 105.6 in all groups respectively, arithmetic was 95.8, 96.2 and 8.4 in all groups respectively, comprehension was 102.4, 104.5 and 107.3 in all groups respectively, verbal quotient was 105.2 in group I, 103.6 in group II and 10.6.7 in group III respectively. Block design was 9.12, 10.2 and 10.4 in all groups respectively, pass along test was 9.4, 9.8 and 10.2 in all groups respectively and the performance quotient was 102.2, 103.5 and 10.5.7 in all groups respectively. The difference was non-significant (P> 0.05). Conclusion: Neuropsychological/cognitive parameters in patients with OCD, depression and healthy control were comparables.